2018
DOI: 10.3389/fpubh.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

National Immunization Campaigns with Oral Polio Vaccine Reduce All-Cause Mortality: A Natural Experiment within Seven Randomized Trials

Abstract: BackgroundA recent WHO review concluded that live BCG and measles vaccine (MV) may have beneficial non-specific effects (NSEs) reducing mortality from non-targeted diseases. NSEs of oral polio vaccine (OPV) were not examined. If OPV vaccination campaigns reduce the mortality rate, it would suggest beneficial NSEs.SettingBetween 2002 and 2014, Guinea-Bissau had 15 general OPV campaigns and other campaigns with OPV plus vitamin A supplementation (VAS), VAS-only, MV, and H1N1 vaccine. In this period, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 47 publications
4
93
0
2
Order By: Relevance
“…An increasing body of evidence suggests that trained immunity plays a critical role in humans. First, an extensive collection of epidemiological data argues that live vaccines such as the BCG vaccine, measles vaccine, smallpox vaccine and oral polio vaccine have beneficial, non-specific protective effects against infections other than the target diseases [40][41][42][43][44][45][46][47] (for a review, see also ReF. 48 ).…”
Section: Trained Immunity In Vertebrates Evidence Of Trained Immunitymentioning
confidence: 99%
“…An increasing body of evidence suggests that trained immunity plays a critical role in humans. First, an extensive collection of epidemiological data argues that live vaccines such as the BCG vaccine, measles vaccine, smallpox vaccine and oral polio vaccine have beneficial, non-specific protective effects against infections other than the target diseases [40][41][42][43][44][45][46][47] (for a review, see also ReF. 48 ).…”
Section: Trained Immunity In Vertebrates Evidence Of Trained Immunitymentioning
confidence: 99%
“…Fourth, boosting with a second dose or further doses of campaign-OPV reduced mortality substantially [33,46].…”
Section: Example: Oral Polio Vaccinementioning
confidence: 98%
“…Second, several studies have shown OPV-campaigns to be associated with a marked decline in the general mortality rate [45][46][47]. Third, OPV campaigns have modified estimated mortality outcomes in studies of other vaccines [45,48].…”
Section: Example: Oral Polio Vaccinementioning
confidence: 99%
“…To date, epidemiological evidence supporting the role of live attenuated vaccines in T cell-mediated H.I. is associated with the measles (55-62), the vaccinia (63-66), and the oral polio vaccine (67)(68)(69). These vaccines reduced overall mortality and/or risk for asthma, malignancies, and unrelated infections.…”
Section: Protection Vs Immunopathologymentioning
confidence: 99%